2022
DOI: 10.46729/ijstm.v3i6.681
|View full text |Cite
|
Sign up to set email alerts
|

Formulation And Evaluation Of Nanoemulgel Clove Leaf Oil (Sygyzium Aromaticum) (L.) Merr & Perry As Anti-Acne

Abstract: Acne also known as acne vulgaris, is an inflammatory condition of the polysebaceous layer that is brought on by the buildup of keratin. Active oil glands under the skin cause acne. Androgen hormones function as a stimulant for this activity. Cloves are herbal plants that contain essential oil chemicals. The chemical composition of clove leaf oil is mainly composed of eugenol. Eugenol has pharmacological effects as antibacterial, analgesic and anti-inflammatory. Nanoemulsion is a nanocarrier that gets a lot of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…This review article discusses the pharmacological activity of nanoemulgel formulations, which include antifungal, antibacterial, and wound-healing properties. Studies in literature indicate that black cumin seed oil nanoemulgel preparations exhibit very strong antibacterial activity (>20 mm), whereas clove leaf oil nanoemulgel preparations show strong antibacterial activity (>10-20 mm) (Dasawanti et al, 2022;Jufri & Natalia, 2014;Sultan et al, 2022). Research by Gadkari et al (2019) found that Tolnaftat is a potent antifungal agent against Trichophyton rubrum, exhibiting a 24 mm inhibitory zone, classified as very strong.…”
Section: Table I and Tablementioning
confidence: 99%
See 1 more Smart Citation
“…This review article discusses the pharmacological activity of nanoemulgel formulations, which include antifungal, antibacterial, and wound-healing properties. Studies in literature indicate that black cumin seed oil nanoemulgel preparations exhibit very strong antibacterial activity (>20 mm), whereas clove leaf oil nanoemulgel preparations show strong antibacterial activity (>10-20 mm) (Dasawanti et al, 2022;Jufri & Natalia, 2014;Sultan et al, 2022). Research by Gadkari et al (2019) found that Tolnaftat is a potent antifungal agent against Trichophyton rubrum, exhibiting a 24 mm inhibitory zone, classified as very strong.…”
Section: Table I and Tablementioning
confidence: 99%
“…The potency of the active ingredient impacts the pharmacological effects of the medication. Higher concentrations of the active substance lead to increased pharmacological activity, namely in terms of antifungal, antibacterial, and wound healing properties (Dasawanti et al, 2022;Jufri & Natalia, 2014). Utilizing excipients like surfactants can enhance the absorption of active compounds, thereby boosting pharmacological action.…”
Section: Table I and Tablementioning
confidence: 99%